Systemic Risk in the European Financial and Energy Sector: Dynamic Factor Copula Approach - Matej Nevrla (Charles University in Prague, Institute of Economic Studies (IES), 2017)
In this paper, we perform analysis of systemic risk in the financial and energy sector in Europe. In our investigation, we work with daily time series of CDS spreads. We employ factor copula model with GAS dynamics of Oh and Patton (2016) for estimation purposes of dependency structures between market participants. Based on the estimated models, we perform Monte Carlo simulations in order to obtain future values of CDS spreads, and then we measure probability of systemic events in given time points. We conclude that substantially higher systemic risk is present within the financial sector than in the energy sector. We also find that the most systemic vulnerable financial and energy companies come from Spain.
Keywords: C53; C55; C58; G17; 330; credit default swap; energy sector; factor copula; financial sector; generalized autoregressive score model; systemic risk